FINANCIAL TECHNOLOGY IN IRAQ: OBSTACLES AND REQUIREMENTS, REGARDING TO SELECTED INTERNATIONAL EXPERIENCES - Hayder M. Kareem Alduhaidahawi; Hussein Ali abed; Mustafa S. Abdulreza (American Journals, 2023)
Recently, the role of financial technologies has been growing in providing financial services and increasing the levels of financial inclusion and the total investment in this sector has increased. These technologies include many advanced solutions and innovations in the financial field that contribute to overcoming the challenges facing the expansion of the provision of financial services.These technologies are in line with the rapid development in commercial exchanges and the massive and rapid developments in the emergence and development of markets and the volume of inter-exchange. The research aims to clarify the most important obstacles and challenges facing financial technology in Iraq and to compare the reality of these technologies with some Arab countries. The research came out with a set of conclusions, the most important of which are: Financial technology has become an economic necessity to keep pace with other economic developments, especially after the spread of electronic transactions significantly as a result of the development of innovations and applications on the mobile phone that perform financial purposes. Financial technology and the shift towards financial digitization are factors in the development of systems and one of the foundations for keeping pace with global developments in the financial field. The research also recommended a set of recommendations, the most important of which is working to develop the infrastructure necessary for the development of financial technology, providing broad institutional support through the establishment of incubators and accelerators to help increase the emerging company in the field of financial technology.
Keywords: Financial technology, financial innovations.